Hamzah Fansuri’s Philosophical Sufism: Wujūdiyyah, the Metaphysics of Creation, and Mystical Taraqqī as an Integrated System of Thought - Muhamad Afif; Jemmy Harto (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2025)
This article explores the philosophical Sufism of Hamzah Fansuri by examining the internal coherence of his thought rather than treating its elements as isolated doctrines. The discussion focuses on three interrelated dimensions that structure his intellectual system: wujūdiyyah as an ontological foundation, the metaphysics of creation as a cosmological framework, and mystical taraqqī as the process of spiritual realization. Using a qualitative library-based method, this study analyzes Hamzah Fansuri’s prose and poetic writings alongside relevant contemporary scholarship through thematic content analysis. The findings suggest that Hamzah Fansuri consistently affirms God as the only Absolute Being, while the universe and humanity are understood as dependent manifestations of divine reality. Creation is not described as a detached, dualistic act, but as a graded process of manifestation (taʿayyun) that preserves divine transcendence. Within this framework, mystical taraqqī represents an inward transformation of human consciousness through the stages of sharīʿa, ṭarīqa, ḥaqīqa, and maʿrifa. This study argues that Hamzah Fansuri’s philosophical Sufism constitutes a systematic and coherent worldview. Interpreting debates on wujūdiyyah as epistemological differences rather than doctrinal conflicts allows for a more balanced understanding of his position within Southeast Asian Islamic thought.